2015
DOI: 10.1080/02648725.2015.1080064
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roles of basal transcription factor 3 in eukaryotic growth and development

Abstract: Basal transcription factor 3 (BTF3) has been reported to play a significant part in the transcriptional regulation linking with eukaryotes growth and development. Alteration in the BTF3 gene expression patterns or variation in their activities adds to the explanation of different signaling pathways and regulatory networks. Moreover, BTF3s often respond to numerous stresses, and subsequently they are involved in regulation of various mechanisms. BTF3 proteins also function through protein-protein contact, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Curiously, at 48 h post transfection the secreted protein levels decreased drastically regardless of changes in mRNA levels prior to this timepoint. Basal transcription factor 3 (BTF3) has been reported to play a significant role in the transcriptional regulation related to eukaryote growth and development [ 89 ]. In LL5 cells it showed increased mRNA levels at 12 h and increased secreted protein level 12 h after mRNA increase.…”
Section: Resultsmentioning
confidence: 99%
“…Curiously, at 48 h post transfection the secreted protein levels decreased drastically regardless of changes in mRNA levels prior to this timepoint. Basal transcription factor 3 (BTF3) has been reported to play a significant role in the transcriptional regulation related to eukaryote growth and development [ 89 ]. In LL5 cells it showed increased mRNA levels at 12 h and increased secreted protein level 12 h after mRNA increase.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that BTF3 is intimately involved in the regulation of a number of biological processes. 11 Its interaction with promoter elements, such as CAAT and TATA box sequences, initiates polymerase transcription by RNA. In addition, previous research has confirmed that BTF3 regulates regulation of the cell cycle as well as apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We next generated PC-3 and DU145 cells stably overexpressing one of the two BTF3 splicing isoforms, BTF3a or BTF3b 17,18 , and subjected them for further functional characterization. Indeed, ectopic overexpression of either BTF3 isoform resulted in markedly enhanced cell growth (Fig.…”
Section: Btf3b Exerts Its Oncogenic Effects Through Transcriptional Rmentioning
confidence: 99%
“…Basic transcription factor 3 (BTF3), also known as the beta subunit of the nascent polypeptide-associated complex, was originally reported to be a member of general transcription machinery and form a stable complex with the RNA polymerase II to initiate transcription 16,17 . BTF3 exists in two splicing isoforms, BTF3a and BTF3b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation